Previous Archaeological Excavations along the "Ostlänken" Railway Corridor 1965-2012: Investigations in a rock carving area (Borg parish, Östergötland). - Swedish National Heritage Board, UV Öst (Uppsala University, 2020)
The Swedish national heritage board performed archaeologic excavations from September 12th to November 18th 1988 and from April 24th to June 2nd 1989. The investigation was done due to road changes of the E4 highway between Lövstad and Norrköping. A total of 80 features and two areas were investigated. Within the excavated area there is one rockcarving, ancient monument 51.

The ZIP-file contains three shapefiles with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as four geo-referenced maps (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Riksantikvarieämbetet utförde arkeologisk utredning under 12 september - 18 november 1988 samt 24 april - 2 juni 1989. Undersökningen utfördes med anledning av ändrad sträckning av E4:an mellan Lövstad och Norrköping.Totalt undersöktes 80 anläggningar och två områden med kulturlager. Inom det undersökta området finns en hällristningslokal, RAÄ 51.

ZIP-filen innehåller data i form av tre shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt fyra georefererade kartor (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Undersökningar i ett hällristningsområde (Borgs socken, Östergötland)
Keywords: ceramics; keramik; finds; fynd; excavation; utgrävning; c-datering; c-datering; HISTORY; HISTORIA; Archaeology; Arkeologi